A phase 3, long-term, open-label safety study of Galcanezumab in patients with migraine - Camporeale, Angelo; Kudrow, David; Sides, Ryan; Wang, Shufang; Van Dycke, Annelies; Selzler, Katherine J.; Stauffer, Virginia L. (BMC neurology, 2018)
Background Galcanezumab, a humanized monoclonal antibody that selectively binds to the calcitonin gene-related peptide, has demonstrated in previous Phase 2 and Phase 3 clinical studies (≤6-month of treatment) a reduction in the number of migraine headache days and improved patients’ functioning. This study evaluated the safety and tolerability, as well as the effectiveness of galcanezumab for up to 12 months of treatment in patients with migraine. Methods Patients diagnosed with episodic or chronic migraine, 18 to 65 years old, that were not exposed previously to galcanezumab, were randomized to receive galcanezumab 120 mg or 240 mg, administered subcutaneously once monthly for a year. Safety and tolerability were evaluated by frequency of treatment-emergent adverse events (TEAEs), serious adverse events (SAEs), and adverse events (AEs) leading to study discontinuation. Laboratory values, vital signs, electrocardiograms, and suicidality were also analyzed. Additionally, overall change from baseline in the number of monthly migraine headache days, functioning, and disability were assessed. Results One hundred thirty five patients were randomized to each galcanezumab dose group. The majority of patients were female (> 80%) and on average were 42 years old with 10.6 migraine headache days per month at baseline. 77.8% of the patients completed the open-label treatment phase, 3.7% of patients experienced an SAE, and 4.8% discontinued due to AEs. TEAEs with a frequency ≥ 10% of patients in either dose group were injection site pain, nasopharyngitis, upper respiratory tract infection, injection site reaction, back pain, and sinusitis. Laboratory values, vital signs, or electrocardiograms did not show anyclinically meaningful differences between galcanezumab dosesOverall mean reduction in monthly migraine headache days over 12 months for the galcanezumab dose groups were 5.6 (120 mg) and 6.5 (240 mg). Level of functioning was improved and headache-related disability was reduced in both dose groups. Conclusion Twelve months of treatment with self-administered injections of galcanezumab was safe and associated with a reduction in the number of monthly migraine headache days. Safety and tolerability of the 2 galcanezumab dosing regimens were comparable. Trial registration ClinicalTrials.gov as NCT02614287 , posted November 15, 2015. These data were previously presented as a poster at the International Headache Congress 2017: PO-01-184, Late-Breaking Abstracts of the 2017 International Headache Congress. (2017). Cephalalgia, 37(1_suppl), 319–374.